Kesetaraan Gender dalam Industri Media: Studi Mobilitas Vertikal Karir Pekerja Perempuan di Riau Televisi - Donny Haris; Jendrius Jendrius; Afrizal Afrizal (Kafa`ah: Journal of Gender Studies, 2019)
The Beijing Platform for Action in 1995 raised awareness, that the mass media contributed greatly to the empowerment and promotion of women. But within the media industry itself, gender equality is a problem. This article discusses the position of women in Riau Television. Of the 12 division leadership positions in Riau Television, there are only four women who occupy manager positions. Using qualitative research methods and using the four women as cases studied, in this article the author reveals the explanation behind only four women occupying managerial positions in the midst of male domination. Framed by the Glass Ceiling Theory the question answered is: What are the pathways in which the four female journalists have succeeded in occupying the position of manager on Riau TV in the midst of male domination? The results of the study show that social channels that enable women to succeed in breaking through the barriers are seen in the policies of the president director as a company leader in promoting them to occupy manager positions. The reality of women who occupy manager positions in Riau Television, is not a portrait that portrays a form of position sharing out of pity. Having the experience, abilities, years of service and achievements of these four women, are a number of requirements that are considered by the president director in deciding to place women in managerial positions.